Entrepreneurship in Tourism Sector in Central European Country: Hospitality Trends in the Czech Republic in 2007 - 2016 - MURA, Ladislav; KAJZAR, Patrik (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).25, 2019)
The aim of this paper is to evaluate the impact of occupancy in accommodation establishments in the Czech Republic at an average pace of real wage growth (%), GDP (%) and unemployment rate (%) in the period 2007-2016. The main sources of information utilized in contributions are based on tourism statistics and selected macroeconomic indicators obtained from the website of the Czech Statistical Office. The data was analysed using SAS software. The authors use regression analysis. It deals with dependence of the quantitative variable on one or more quantitative variables. The main results of this survey indicate an increase of  occupancy in collective acommodation establishements in the Czech Republic between 2007 - 2016, as well as a moderate increase was detected in  real wages and the GDP. While detecting an  increase of  occupancy in collective acommodation establishements in the Czech Republic, the fall of unemployment rate was recognized.